Socio-Technological Transitions in Agriculture: A Bibliometric and Systematic Analysis of Global Trends and Future Directions - Hariyanti Hamid; Suparman Abdullah; Rahmat Muhammad; Herman Dema (Jurnal Sains Agribisnis, 2026)
The agricultural sector is undergoing rapid transformation driven by digital innovation, climate change, sustainability challenges, and increasing food security demands. Understanding how technological innovation interacts with social and institutional change has become essential for supporting sustainable agricultural development. This study aims to examine the evolution of socio-technical transition research in agriculture through an integrated bibliometric analysis and systematic literature review approach. Data were collected from the Scopus database, resulting in a final dataset of 777 publications published between 2020 and 2024. Bibliometric analysis was conducted using VOSviewer to identify publication trends, collaboration networks, conceptual structures, and intellectual foundations of the field. The results indicate a substantial increase in scientific publications, rising from 53 documents in 2020 to 157 documents in 2024, reflecting growing global interest in agricultural transformation. China and the United States emerged as the leading contributors to scientific production, while increasing participation from developing countries highlights the global relevance of socio-technical transitions. Keyword co-occurrence analysis revealed dominant themes related to digital agriculture, technology adoption, sustainability, climate adaptation, social inclusion, and agricultural innovation systems. Co-citation analysis demonstrated strong intellectual connections among digital farming, sustainability transition, and innovation studies. The findings highlight a shift from technology-centered perspectives toward more integrated approaches emphasizing governance, institutional support, and equitable access to innovation. This study provides a comprehensive knowledge map and identifies future research directions for promoting inclusive and sustainable agricultural transitions.